Exploring the Utilization of Artificial Intelligence on Educational Efficiency: A Field Study in Riyadh - Al-Kahtani, Sarah Hamoud (Journal of Educational and Psychological Sciences, 2024)
The integration of artificial intelligence (AI) in various domains has revolutionized the way individuals approach problem-solving and decision-making. In the field of education, AI has emerged as a powerful tool with the potential to enhance learning experiences and improve educational outcomes..The study aimed to explore the utilization of using artificial intelligence applications on achieving the effectiveness of education and on the success of the educational process in general.This study was conducted at an educational institiution as a case study in Riyadh, Saudi Arabia. The researcher used the descriptive-analytical approach by applying a questionnaire as a tool to collect data for the study.The researcher applied an electronic survey in the period from December of the academic year 2023 to February 2024. The primary data included information about the sample for the study according to the independent study variables, which are (profession- specialization applications, the support from the side of the institution administration to utilize artificial intelligence, factors that helped in the transition to the utilization of artificial intelligence applications and the difficulties faced by students, teachers, and administrators in benefiting from artificial intelligence applications.The study found significant correlations between AI application utilization and support from the side of the educational institution’s administration, including encouragement, resource provision, and addressing challenges faced by female students and teachers in accessing AI-related resources. Based on the results and the growing demand for using these applications and this technology, the researcher recommends: raising awareness of AI’s societal impact and ethical challenges, implementing a robust regulatory framework, and innovating a national application of AI-based on data governance. investing in AI ethics research and tools for monitoring ethical implications.